Molecular Genetics, Genetic Testing, Novel Genome Sequencing Technologies - Gerard Pals (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
AbstractWith the advance of genomic technologies, we are now able to detect genetic variations in patients with high accuracy, whole genome scale and relatively cost-effective. This offers an opportunity for altering medical practice fundamentally as well as insurance policy. Although clinicians, scientists, and health policy makers still have to deal how to interpret and handle the results that sometimes come with ambiguity and uncertainty, recent advances especially in the western world have integrated genetic tests and molecular genetic analysis for clinical management of patients. In this session, we will discuss and review the range of methods currently used in clinical setting as well as potential emerging methods in clinical molecular genetic diagnostics. Advantages and disadvantages of each methods will be carefully discussed especially application in regions of the world that have more limited access for molecular genetic tests including next generation sequencing. Outline of implementation challenges for molecular genetic tests both in term of health economics and clinical management will also be discussed.